Stable Slope Design Based On Limit Equlibrium Method (Lem) And Finite Element Method (Fem) At Pit X, Lahat, South Sumatra - BAGASKORO, MUHAMAD NUR; Irvan Shopian, Raden; Ramadian, Aldrin (Journal of Geological Sciences and Applied Geology, 2023)
Coal mining process using open pit mining method is closely related to slope stability. A slope whose stability is disturbed will have a higher potential for landslides. The slope stability analysis in this research is conducted by Limit Equilibrium Method (LEM) with the calculation of Morgenstern-pice slice method and Finite Element Method (FEM) with the calculation of Shear Strength Reduction. The highwall simulation was modeled with a Bench height of 10 meters, Bench width of 6.5 meters and bench tilt angle varying between 30°, 45°, 60° and groundwater condition using steady state FEA. From the results of the LEM analysis on the highwall with a bench tilt angle of 30 °, 45 °, 60 ° has a safety factor value of 1.005; 0.76; 0.584. While the results of the FEM analysis on the highwall with a bench tilt angle of 30 °, 45 °, 60 ° have a Strength Reduction Factor value of 0.98; 0.72; 0.57. Comparison of the safety factor values of the two methods has an average difference of 1-2%. This is because the FEM takes into account the stress-strain in the material which describes how the material behaves. The stable slope design based on LEM is a highwall slope with a Bench slope angle of 22° which has a safety factor value of 1.478 and based on FEM is a highwall slope with a Bench slope angle of 22° which has a Strength Reduction Factor value of 1.42.